The cost of successful antiviral therapy in hepatitis C patients: a comparison of IFN-free versus IFN-based regimens at an individual patient level in Australia - Lee AS; van Driel ML; Crawford DHG (Dove Medical Press, 2017)
Allister Sebastian Lee,1 Mieke L van Driel,2 Darrell HG Crawford3,4 1Faculty of Medicine, 2Primary Care Clinical Unit, Faculty of Medicine, 3School of Clinical Medicine, Faculty of Medicine, University of Queensland, 4Gallipoli Medical Research Foundation, Greenslopes Private Hospital, Brisbane, Australia Background: Chronic hepatitis C remains a major global health burden with serious long-term consequences if left untreated. Recently the treatment standard of care has shifted to new interferon (IFN)-free drug regimens, which have been shown to be safe and effective. The aim of our study was to assess and compare medical resource utilization and costs of successfully treating patients with IFN-based and IFN-free therapies in Australia. Methods: We performed a retrospective chart review of 30 HCV-infected patients successfully treated with IFN-based therapy between 2013 and 2015. We also generated a model for a virtual group of 100 genotype 1 (GT1) and 100 genotype 3 (GT3) patients treated with IFN-free therapy derived from national guidelines and clinical trial data. Results: In comparison to virtual patients receiving IFN-free therapy, our IFN-treated patients on average had distinctively more liver clinic visits and blood tests. However, mean total cost per patient was $19,164 and $85,300 (AUD) more for GT1 and GT3 patients receiving IFN-free therapy, respectively. This difference was largely accounted for by higher antiviral drug costs. Of our 30 patients treated with IFN, total mean cost per patient during the study period was $33,595. Conclusion: Resource utilization is lower with IFN-free treatment, which reflects the reduced need for patient monitoring and improved side-effect profile of these new drugs. However, total costs are still largely dominated by antiviral drug costs, representing a huge burden on national budgets. Our insight into resource utilization and costs associated with both types of treatment can serve as a reference for future studies. Keywords: antiviral treatment, chronic hepatitis C, comparison, costs, real-life setting, resource utilization